Digital Modul IPA Terpadu berbasis Tematik dengan Pokok Bahasan Penyelaman - Indica Okyranida; Ria Asep Sumarni (Neolectura, 2021)
Digital module is a module that can be opened using gadgets, the appearance of modules such as sheets of books. This digital module is created using the Flip Pdf Builder application. Digital module Integrated dive theme is made with sound explanation material and learning video in accordance with the theme of diving. . Voice recordings of explanations of the material on this digital module can be listened to by students, so that students not only read but can listen to the material. Explanatory sound can be set if you do not want to listen to the sound, can click the sound icon so that the sound is off. Digital modules are more interesting because there are explanatory videos that can help students in understanding diving materials. The video connects to the youtube link when we click on the youtube icon. The youtube video is adapted to the materials that match the theme of the dive.